THORACIC SURGERYResults of the surgical treatment of patients suffering from bronchopulmonary carcinoid tumors in the Department of Thoracic Surgery in Bystra in the period 1990-2011 - Wiencek-Weiss, Alina J.; Wandzel, Piotr; Rogoziński, Paweł B.; Kaczor, Tomasz; Ryszka, Józef; Brózda, Witold; Bubel, Adam; Bruliński, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: The new classification and terminology concerning neuroendocrine tumors, according to the European Neuroendocrine Tumor Society (ENETS) guidelines, were not universally accepted for bronchopulmonary carcinoids. That is why the term “carcinoid” is still being used in its traditional meaning. Precise identification of bronchopulmonary carcinoid subtypes constitutes an important prognostic factor. Aim of the study : The aim of the study was to present the results of bronchopulmonary carcinoid surgical treatment conducted at the Department of Thoracic Surgery in Bystra, to assess the surgery material in accordance with the WHO 1999 (Travis) classification, and to compare the clinical courses of typical and atypical carcinoid tumors. Material and methods : The analysis included 159 patients aged 18-77, treated surgically due to bronchopulmonary carcinoids in the years 1990-2011. Reassessment of histological preparations was carried out according to the WHO 1999 (Travis) and International Association for the Study of Lung Cancer (IASLC) classification; check-ups of the treated patients were performed as well. Disease-free interval (DFI) and overall survival were assessed with the Kaplan-Meier method; the clinical course of typical and atypical carcinoids was compared. Results : As a result of the histological reassessment, 142 patients (88.3%) were diagnosed with typical carcinoids, and 17 patients (11.7%) with atypical carcinoids. During the follow-up period, local disease recurrence occurred in 8 (4.9%) patients, distant metastases in 13 (8.2%) patients. There were 26 (16.4%) instances of death – 2 because of other malignant neoplasms. The DFI median (p = 0.00003) and overall survival (p < 0.00001) were significantly longer in patients with typical carcinoids than in patients with atypical types of the tumor. Conclusions : The histological subtype of a bronchopulmonary carcinoid tumor is the dominant prognostic factor in assessing the DFI and the 5-year survival after surgery.